Management and outcome in patients with below knee soft tissue injuries - Sachdev, Gurvansh S.; Rajan, Manu; Dvivedi, Sanjay; Agrawal, Saurabh; Rawat, Kinnari A. V. (International Surgery Journal, 2018)
Background: Treatment of lower limb injuries pose a great challenge. Debridement is the key to success in the management of major limb injuries followed by soft-tissue coverage in the form of suturing, skin grafts, or flaps. Our aim is to study the management of various below knee soft tissue injuries. Methods: The study was conducted in the Department of Surgery, Himalayan Institute of Medical Sciences (HIMS), Swami Ram Nagar, Dehradun, over a period of 12 months. Subjects were recruited from patients presenting in Emergency/Surgery OPD, HIMS, Dehradun with a primary diagnosis of below knee soft tissue injuries. A total of 64 patients were included in the study. Results: Primary closure was done in 6 wounds and coverage in rest, with maximum in the form of split skin graft. Abrasion wounds were managed without any surgical intervention. Reconstructive surgery was performed two or more times in 39.06% patients. Local complications were seen in 23.43% of patients and general complications AKI and Tetanus in 2patients.68.75% of patients with local complications were observed to have contaminated wound status at the time of presentation. The average duration of hospital stays ranged between 3 to 56 days. Majority of the patients were discharged within 1 to 3 weeks with mean duration of hospital stay being 17.82±10.95 days. Conclusions: Proper debridement, early coverage of wounds and prompt identification and management of complications is the key to success in the management of lower limb trauma.